2008
DOI: 10.1007/s10643-008-0275-y
|View full text |Cite
|
Sign up to set email alerts
|

Using Microsoft® PowerPoint™ to Support Emergent Literacy Skill Development for Young Children At-Risk or Who Have Disabilities

Abstract: The increasing availability and use of technology applications for teaching emergent literacy skills in early childhood education settings nationwide requires that early childhood education professionals develop skills with readily available software programs. This paper provides general recommendations in using Microsoft Ò PowerPoint TM to support emergent literacy skill development for young children at-risk or who have disabilities. Specific suggestions are presented in the areas of phonological awareness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 7 publications
(8 reference statements)
0
14
0
Order By: Relevance
“…As illustrated in the preceding vignettes, young children live and participate in twenty-first century daily life activities that are permeated with the presence of a wide range of technologies (Parette et al 2008a). In fact, our world has changed so markedly in recent decades with regard to the use and impact of technology, that more than 10 years ago Conn (cited in Tapscott 1998) observed that technology is ''like the air'' (p. 39) for the current generation of children.…”
Section: Role Of Technology In Today's Worldmentioning
confidence: 99%
“…As illustrated in the preceding vignettes, young children live and participate in twenty-first century daily life activities that are permeated with the presence of a wide range of technologies (Parette et al 2008a). In fact, our world has changed so markedly in recent decades with regard to the use and impact of technology, that more than 10 years ago Conn (cited in Tapscott 1998) observed that technology is ''like the air'' (p. 39) for the current generation of children.…”
Section: Role Of Technology In Today's Worldmentioning
confidence: 99%
“…PowerPointTM has many features to facilitate acquisition of these skills, including the ability of the teacher to modify such features as color, pictures, sounds, animation, slide design, and slide transition. As a result, educators can help young children develop initial sound fluency by making them aware of words that start with the same sound, or alliterations [16]. Furthermore, phonemic orthography that has to do with the relationships between letters and their associated sounds [17] can be taught with the connection between a letter and its associated sound.…”
Section: Supporting Children With Literacy Difficultiesmentioning
confidence: 99%
“…PowerPoint TM is popular because many early childhood education professionals are already familiar with its content and use (Grabe and Grabe 2007; Jefferson County Schools n.d.; Parette et al 2008). Its use may enhance the learning experiences of young children because it has features that are common in young children's home and other environments where technology is used (e.g., animation, color, large screen presentation format) (Jewitt 2006;Mayer 2005;Turbill and Murray 2006).…”
Section: Microsoft ò Powerpoint Tm In the Early Childhood Curriculummentioning
confidence: 99%
“…As many early childhood professionals recognize, there are numerous features in PowerPoint TM that are helpful in teaching word recognition to children at risk (see Parette et al 2008 for a discussion of PowerPoint TM features). These include the ability to add images, sound, and animation-features that can capture the attention of young children at risk (Jewitt 2006).…”
Section: Sequential Steps In Teaching Word Recognition Using Powerpoimentioning
confidence: 99%
See 1 more Smart Citation